KOMUNIKASI TRANSENDENTAL APLIKASINYA SEPERTI APA? - Gunadi, YS (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2007)
Unusualy, the elements of communication activities there are com-municator, message, and communicant. But, why is commu- nication religion as prayer believed to the God? God is not material like the man, not can see by our eyes. If every one praying to the God, where is God, God not clear in front our faces. Prayer activities belong communication models or not?Nearly intelectualities of communication make the definition, pra-ying activitities, althought not clear who was the communicant,but is communication. The mane of communications activities ia trancendental communication. The hung of transcendental com- munication to tell to you with the story illustrationat unders.